Abuse of Authority in Procurement Under the Corruption Law - Asis; Devi Mutiara Sanni (Law Research Review Quarterly, 2026)
Nowadays, the practice of corruption in government procurement of goods and services is becoming increasingly sophisticated, and it is not uncommon for perpetrators to hide behind formal procedures such as the determination of the Self-Estimated Price (Harga Perkiraan Sendiri/HPS). This becomes legally justifiable because Article 26, Paragraph (6) of Presidential Regulation No. 16 of 2018 states that the HPS is not the basis for calculating the amount of state financial loss. However, the crime of corruption in the context of procurement does not lie in the numerical difference, but rather in the malicious intent (mens rea) when abusing authority in the process of determining the HPS. This study uses a normative legal research method with a statutory and case approach. This research addresses the following issues: 1). Can the inflation of the Self-Estimated Price (HPS) fulfill the element of "abuse of authority" in Article 3 of the Corruption Eradication Law, even though it is not used as the basis for calculating state losses? 2). Is proving malicious intent (mens rea) in the HPS determination process more essential to prosecute corruption perpetrators compared to proving the amount of state financial loss? In this study, it was found that an unreasonable HPS is not a representation of state loss, but rather an instrumentum delicti a tool intentionally created to facilitate the crime. The main finding shows that the act of inflating the HPS perfectly fulfills the element of "abusing authority" in Article 3 of the Corruption Eradication Law, as this action creates a corrupt opportunity for other parties. Therefore, it is imperative that law enforcement officials prioritize investigations into the process and methodology of HPS formulation to prove conspiracy and abuse of authority, rather than being trapped in debates about calculating state losses based on estimations.